Distribution of potato mosaic viruses on plants of the Petota Dumort. section of Solanum L. in the VIR collection - E. V. Rogozina; A. A. Gurina (Труды по прикладной ботанике, генетике и селекции, 2023)
Background. Potato due to its vegetative propagation is affected by viruses, among which potato viruses Y (PVY), S (PVS) and M (PVM) are spread across all Russia’s territory. The VIR collection presents the diversity of the potato gene pool, including potato cultivars and related tuber-forming species. Diagnostics of viral infections in plants saved for several years by obtaining tuber reproductions is an important part of the work on the conservation and sustainable utilization of the potato gene pool.  The purpose of the work was to evaluate the distribution of PVX, PVY, PVS and PVM on plants of potato cultivars and related Solanum spp. in the VIR field collection.   Material and methods. Evaluation covered 315 accessions representing all groups of the potato gene pool. Diagnosis by enzyme-linked immunosorbent assay (ELISA) was carried out on plants that did not display symptoms of a virus infection. The Russian test system of RPA “BioTechnologies” and foreign one of Bioreba AG (Switzerland) were used. Statistical data processing was performed by the Statistica StatSoft 13 program.   Results. Mosaic viruses are distributed with different frequencies on potato plants in the field collection: PVM dominates, detected in 64% of potato accessions; PVY is found in 41 %, PVX on 24 %, and PVS in 18 % of accessions. The connection between the botanical and taxonomic origin of potato accessions and their infection with viruses has been confirmed. Among wild species, more than half of accessions, while among cultivated species, only 5% are affected by XBK. PVM, on the contrary, was detected in a significant part (77–91%) of cultivated potato accessions. and much less frequently (16%) in accessions of wild species. Cvs, ‘Grand’, ‘Krasa Meshchery’, ‘Yantar’ and ‘Nur-Alem’, hybrids 99-1-3, 952-35 and 914-5-2018, accessions of wild species from North America, and cultivated species Solanum goniocalyx Juz. et Buk. (k-9922) are not affected by viruses.